Rectangular Dielectric Resonator Antennas Theory and Design - Yaduvanshi, Rajveer S.; Parthasarathy, Harish (Springer India : Imprint: Springer, 2016)
This book covers resonating modes inside device and gives insights into antenna design, impedance and radiation patterns. It discusses how higher-order modes generation and control impact bandwidth and antenna gain. The text covers new approaches in antenna design by investigation hybrid modes, H_Z and E_Z fields available simultaneously, and analysis and modelling on modes with practical applications in antenna design. The book will be prove useful to students, researchers and professionals alike.